Analisis Kesalahan Umum dalam Menulis Bahasa Arab pada Mahasiswa Baru - Maylisa Putri Tambunan; Nadya Amalia Rizky Panjaitan; Rabiatun Adawiah; Risti Nurul Fikriyah; Sakholid Nasution (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This research was carried out with the aim of this research being to analyze what errors there are in Arabic writing skills for beginner students. This research uses a qualitative descriptive method with observation, documentation and data analysis techniques. The results of the research found errors in Arabic writing skills for beginner students.